Peningkatan Literasi Masyarakat Desa Melalui Perpustakaan Digital Berbasis QR Code pada Rumah Edukasi Desa Penambangan, Curahdami, Bondowoso - Nurul Faiqotuz Zakyyah; Masrurotus Sa’adah; Sekar Farah Firdausi; Nurul Fitria; Alfian Nur Shidiq; Mohammad Tohir Ali; Olyvia Zalianti; Nazhifah Mildani Nuruddhuha; Nur Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aims to improve the literacy of residents in Penambangan Village through the implementation of a QR Code-based digital library at the Educational Center. The background of this program lies in the low level of literacy in rural areas, which is strongly influenced by the limited access to reading materials and the absence of library facilities. In the current digital era, the need for fast, easy, and affordable access to information has become increasingly important. Therefore, the application of simple technology such as QR Codes is considered an innovative solution to bridge the literacy gap between rural and urban communities. The method used in this activity was Participatory Action Research (PAR), which emphasizes active involvement of the community. The stages of the program consisted of initial observation to identify literacy needs, collaborative planning with local residents, implementation of the QR Code-based digital library, and reflection to evaluate achievements and challenges. This method ensured that the community was not only an object but also an active subject in the process of improving literacy. The results show an increase in reading interest and access to digital literacy, especially among young people. QR Codes installed at several strategic points enabled residents to access various digital reading resources using smartphones. Nevertheless, some obstacles were identified, including limited internet infrastructure and low digital literacy among the older population. Despite these challenges, the program successfully demonstrated that simple, technology-based approaches can significantly enhance literacy in rural areas. In conclusion, the implementation of a QR Code-based digital library supported by a PAR approach can serve as an effective alternative to increase literacy in rural communities. The success of the program strongly depends on collaboration among local residents, academics, and stakeholders to ensure its sustainability in the long term.